The Glycol Cleavage in Natural Product Synthesis: Reagent Classics and Recent Advances - Schmidt, Andrea-Katharina C.; Stark, Christian B. W. (Synthesis, 2014)
This review focuses on the application of glycol cleavage reactions in the synthesis and derivatization of complex natural products. Reagent classics as well as recent developments are discussed.1 Introduction2 Mechanistic Aspects3 Reagents and Examples3.1 Periodate and Hypervalent Iodine3.1.1 Periodic Acid and Periodates3.1.2 Periodate on Wet Silica Gel3.1.3 Phenyliodine Diacetate3.1.4 Other Iodine Reagents3.2 Lead Tetraacetate3.3 Chromium Reagents3.3.1 Pyridinium Chlorochromate3.3.2 Other Chromium Reagents3.4 Ruthenium Reagents3.4.1 Tetra-n-propylammonium Perruthenate3.4.2 Other Ruthenium Reagents3.5 Manganese Reagents3.5.1 Manganese(III) Acetate3.5.2 Manganese Dioxide3.5.3 Other Manganese Reagents3.6 Miscellaneous4 Conclusion
Keywords: oxidation; diols; glycol cleavage; natural products; total synthesis